HUBUNGAN ANTARA MEROKOK DENGAN HIPERTENSI DI PUSKESMAS KAWANGKOAN - Umbas, Irene Megawati; Tuda, Josef; Numansyah, Muhamad (JURNAL KEPERAWATAN, 2019)
Abstrack: A person can be said to be a smoker if he has smoked at least 100 cigarettes.Someone who smoked cigarettes more than one pack of cigarettes per day to 2 times moresusceptible to hypertension than those who do not smoke. Danger hypertension triggersdamage to organs including: kidney, brain, heart, eyes, cause vascular resistance and stroke.The purpose of this study is to know relationship between between smoking and hypertensionat Public Health Center Kawangkoan. The method of this study uses cross sectional studydesign. The sample of this study amounted to 74 students with total sampling method. Theresults of this study were obtained from 74 respondents studied the majority of smokers werehypertensive, first degree 19 respondents, hypertension high normal 13 respondents,hypertension degree II 11 respondents. Heavy smoker degree II hypertension 18 respondents,first degree hypertension 9 respondents, hypertension normal height of 4 respondents, usingthe chi-square test at the level meaning 95%, it was found that the value of p-value was 0.016smaller than the significant value 0.05. The conclusion of this study is that there is arelationship between Smoking and Hypertension at Public Health Center Kawangkoan.Keywords: Smoking, HypertensionAbstrak: Seseorang dikatakan perokok jika telah menghisap minimal 100 batang rokok.Seseorang menghisap rokok lebih dari satu bungkus rokok per hari menjadi 2 kali lebih rentanterhadap hipertensi dari pada mereka yang tidak merokok. Bahaya hipertensi memicurusaknya organ tubuh diantaranya: ginjal, otak, jantung, mata, menyebabkan resistensipembuluh darah dan stroke. Tujuan: Studi ini untuk mengetahui hubungan antara Merokokdengan Hipertensi di Puskesmas Kawangkoan. Metode: Studi ini menggunakan desainpenelitian cross-sectional. Sampel: Studi ini berjumlah 74 responden dengan pengambilansampel Total-Sampling. Hasil: Dari penelitian ini, didapatkan dari 74 responden yang ditelitisebagian besar perokok sedang hipertensi derajat I 19 responden, hipertensi normal tinggi 13reponden, hipertensi derajat II 11 responden. Perokok berat hipertensi derajat II 18 responden,hipertensi derajat I 9 responden, hipertensi normal tinggi 4 responden, dengan menggunakanuji chi-square pada tingkat kemaknaan 95%, didapat bahwa nilai p-value adalah 0,016 lebihkecil dari nilai signifikan 0,05. Kesimpulan: Dari penelitian ini bahwa terdapat hubunganantara Merokok dengan Hipertensi di Puskesmas Kawangkoan.Kata Kunci: Merokok, Hipertensi